O currículo na formação de professores de artes visuais na perspectiva hermenêutico-dialética - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
The thesis is the result of targeted research in the line of research 'Teaching and Learning', the Program of Graduate Studies in Education at the level of PhD, State University of Ponta Grossa. It appears that assumption justifies a curriculum design in the formation of Visual Arts teachers in a hermeneutic-dialectic perspective? The thesis has the objective to understand the curriculum basics in a hermeneuticdialectical perspective on the formation of Visual Arts teachers. For this, we seek to meet the following specific objectives: (i) establish a critical look at the theoretical and curricular foundations in the current context of teacher education Visual Arts of Paraná IEES; (II) to address the fundamentals of education in hermeneutic-dialectical perspective as a basic assumption curriculum; and (III) based on the previous objectives, assumptions scoring a resume in hermeneutic-dialectical perspective on the formation of Visual Arts teachers. The methodological proposal of the thesis is based on the epistemological conjunction between hermeneutics and dialectics, while reflexive movement that approaches its object. In the field of Visual Arts and the training of teachers, the synthesis of hermeneutics and dialectics result in interpretative critical of the social and historical reality. The methodological procedures refer to the critical interpretation of published documents of public nstitutions of the State of Paraná and the use of library materials. It is argued that, in view of a theoretical foundation hermeneutics and dialectics, the curriculum can be a strategic educational tool and political human formation. Thus, it is understood that the formation of the teacher of Visual Arts requires a process to review and update their theoretical and curricular base, particularly in the state of Paraná. This is to reflect, interpret, analyze, criticize and propose a curriculum design to the formation of Visual Arts teachers, making possible the realization of a society project supported the ideals of emancipation, autonomy and critical awareness. The curriculum needs to be built communicative and democratically based on shared understanding of the subjects on the praxis of life. The hermeneutic-dialectical conception of education curriculum for Visual Arts teachers aims to provide aesthetic and artistic criticism and emancipatory experiences.
The curriculum in the formation of visual arts teachers in the hermeneutic- dialectic perspective
Keywords: currículo; hermenêutica; dialética; formação de professores; Artes Visuais; curriculum; hermeneutics; dialectic; teacher formation; Visual arts; CNPQ::CIENCIAS HUMANAS::EDUCACAO